177k views
1 vote
An equation is shown below:

4(x − 3) − 5(x + 1) = 3

Which statement shows a correct next step in solving the equation?

The equation can become 4x − 3 − 5x + 1 = 3 by applying the associative property of multiplication.
The equation can become 4x − 3 − 5x + 1 = 3 by applying the distributive property.
The equation can become 4x − 12 − 5x − 5 = 3 by applying the distributive property.

1 Answer

3 votes

Answer:

The equation can become 4x − 12 − 5x − 5 = 3 by applying the distributive property.

Explanation:

By applying the distributive law to this equation, we can produce the equation :

4x − 12 − 5x − 5 = 3;

The distributive property is a mathematical function in which each element in the parentheses is multiplied by the one outside of it;

4(x − 3) − 5(x + 1) = 3

In the equation;

4 distribute over the first parentheses and -5 over the second one;

So we expand;

4x - 13 - 5x -5 = 3

In distributive property, expansion simply takes place.

User KoleS
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.